Animal Welfare Certification For Laying Hens: Compliance With The Legal Prohibition Of Mistreatment In Brazil - Yuri Fernandes Lima (Universitat Autonoma de Barcelona. Facultat de Dret, 2019)
This article aims to analyze the effectiveness of animal welfare certification for compliance with the legal prohibition of cruelty and mistreatment in the egg industry. I analyze the conditions of conventional cage systems, the legal protection to laying hens in Brazil, and the animal welfare certification for laying hens. I conclude that the existing welfare certification for laying hens is enough to ensure the accomplishment of the law, but it is necessary to consider ways to stimulate producers to obtain this certification and, therefore, to change their mode of production, providing a high level of welfare for laying hens.